Zanubrutinib in patients with previously treated B-cell malignancies intolerant of previous Bruton tyrosine kinase inhibitors in the USA: a phase 2, open-label, single-arm study - Shadman, Mazyar; Flinn, Ian W; Levy, Moshe Y; Porter, Ryan F; Burke, John M; Zafar, Syed F; Misleh, Jamal; Kingsley, Edwin C; Yimer, Habte A; Freeman, Benjamin; Rao, Subramanya S; Chaudhry, Arvind; et al. (The Lancet. Haematology, 2023)
We hypothesised that zanubrutinib, a highly selective next-generation Bruton tyrosine kinase (BTK) inhibitor, would be a safe and active treatment for patients intolerant of ibrutinib, acalabrutinib, or both. We aimed to assess whether zanubrutinib would prolong treatment duration by minimising treatment-related toxicities and discontinuations in patients with previously treated B-cell malignancies. This ongoing, phase 2, multicentre, open-label, single-arm study was done in 20 centres in the USA. Patients aged 18 or older with previously treated B-cell malignancies (chronic lymphocytic leukaemia, small lymphocytic lymphoma, mantle cell lymphoma, Waldenström macroglobulinaemia, or marginal zone lymphoma) who became intolerant of ibrutinib, acalabrutinib, or both, were orally administered zanubrutinib 160 mg twice daily or 320 mg once daily per investigator. The primary endpoint was recurrence and change in severity of ibrutinib or acalabrutinib intolerance events based on investigator-assessed adverse events. Secondary endpoints were investigator-assessed overall response rate; duration of response; disease control rate; and progression-free survival. Analyses included all patients who received any dose of the study drug. This study is registered with ClinicalTrials.gov, NCT04116437. Between Oct 14, 2019, and Sept 8, 2021, 67 patients (36 [54%] men and 31 [46%] women) who were intolerant of ibrutinib (n=57; cohort 1) or of acalabrutinib or acalabrutinib and ibrutinib (n=10; cohort 2) were enrolled. 63 (94%) patients were White, one (2%) had multiple ethnicities, and three (5%) had unreported or unknown ethnicity. Most intolerance events (81 [70%] of 115 for ibrutinib; 15 [83%] of 18 for acalabrutinib) did not recur with zanubrutinib. Of the recurring events, seven (21%) of 34 ibrutinib intolerance events and two (67%) of three acalabrutinib intolerance events recurred at the same severity with zanubrutinib; 27 (79%) ibrutinib intolerance events and one (33%) acalabrutinib intolerance event recurred at a lower severity with zanubrutinib. No events recurred at higher severity. No grade 4 intolerance events recurred. 64 (96%) of 67 patients had one or more adverse events with zanubrutinib; the most common adverse events were contusion (in 15 [22%] of 67 patients), fatigue (14 [21%]), myalgia (ten [15%]), arthralgia (nine [13%]), and diarrhoea (nine [13%]). Atrial fibrillation occurred in three (4%) patients (all grade 2). Eight (12%) of 67 patients had serious adverse events (anaemia, atrial fibrillation, bronchitis, COVID-19, COVID-19 pneumonia, febrile neutropenia, salmonella gastroenteritis, transfusion reaction, trigeminal nerve disorder, and urinary tract infection). No treatment-related deaths occurred. The median follow-up time was 12·0 months (IQR 8·2-15·6). Among the 64 efficacy-evaluable patients, disease control rate was 93·8% (60; 95% CI 84·8-98·3) and overall response rate was 64·1% (41; 95% CI 51·1-75·7). The median duration of response was not reached; the 12-month event-free duration of response rate was 95·0% (95% CI 69·5-99·3). Similarly, median progression-free survival was not reached; 18-month progression-free survival was 83·8% (95% CI 62·6-93·6). Patients intolerant of previous BTK inhibitors have limited treatment options. These results suggest that zanubrutinib, a safe and viable treatment for patients with B-cell malignancies, might fill that unmet need for those who exhibit intolerance to ibrutinib or acalabrutinib. BeiGene.